2021
DOI: 10.1186/s12876-021-01960-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between regular arrangement of collecting venules and Helicobacter pylori status in routine endoscopy

Abstract: Background The sensitivity of regular arrangement of collecting venules (RAC)-positive pattern for predicting Helicobacter pylori (H. pylori)-negative status greatly altered from 93.8 to 48.0% in recent two decades of various studies, while the reason behind it remained obscure. The aim of this study was to investigate the value of RAC as an endoscopic feature for judging H. pylori status in routine endoscopy and reviewed the underlying mechanism. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The findings of the Kyoto classification of gastritis indicate H. pylori infection and non-infection. In addition, several studies have suggested that mucosal edema, spotty redness, diffuse redness, nodularity, and RAC loss are associated with H. pylori infection [ 7 , 10 , 15 , 16 ]. In our study, these endoscopic features were considerably more apparent in H. pylori -infected patients, whereas uninfected patients showed increased RAC presence, fundic gland polyp, linear streak, and raised erosion.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the Kyoto classification of gastritis indicate H. pylori infection and non-infection. In addition, several studies have suggested that mucosal edema, spotty redness, diffuse redness, nodularity, and RAC loss are associated with H. pylori infection [ 7 , 10 , 15 , 16 ]. In our study, these endoscopic features were considerably more apparent in H. pylori -infected patients, whereas uninfected patients showed increased RAC presence, fundic gland polyp, linear streak, and raised erosion.…”
Section: Discussionmentioning
confidence: 99%
“…CVs represent blood vessels that begin at the level of the gastric foveolar layer and descend to merge with the submucosal plexus to form a complex and tree-like three-dimensional structure. Their morphology and arrangement are intricately linked to the presence and organization of gastric foveoli and body glands (18). Kishino et al (19) documented a case of early-stage AIG.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of RAC as an indicator of non-infection has been reported in both in Japan[ 17 , 18 ] and several other countries[ 19 - 21 ], including in the west[ 22 - 24 ], as shown in Table 2 . Two recent meta-analyses reported that the sensitivity and specificity of RAC for predicting non-infection were 78%-80% and 94%-97%, respectively[ 25 , 26 ].…”
Section: H Pylori Infection In the Kyoto Classificationmentioning
confidence: 99%
“…Further research is required to confirm these findings. RAC provides high kappa values of intra-observer and inter-observer agreements of 0.88-0.91 and 0.74-0.79, respectively[ 21 , 68 ]; however, agreement between the other endoscopic findings needs to be clarified.…”
Section: Future Perspectives In Kyoto Cassificationmentioning
confidence: 99%